Participation Banks in Turkey: Issues and Proposes Strategies Based on SWOT Analysis - Zulfahmi Zulfahmi; Abrista Devi; Eyup Asker; Rusni Hassan (Universitas Muhammadiyah Yogyakarta, 2021)
Turkey has a long history in Islamic civilisation. However, there is still lack of research to examine participatory banks in Turkey. This is despite the fact that the legacy of strong Islamic law, the majority Muslim population, and the strategic location of the country have failed to serve as catalyst to boost market share of participation banks in the country. This study is aimed at developing priority ranking of SWOT factors and strategies on the participatory bank development in Turkey. Data are collected from experts and practitioners of Participation (Islamic) bank in Turkey. Analytic Network Process (ANP) is used as the methods of analysis. The finding shows that the aspects of participatory banks in Turkey are derived from strengths, opportunities, weakness and threats factors. Sharia board is the main strength of this study, while inadequate competitive product is the main weakness. In the future, government support stands as the first priority from opportunity aspect. Islamic bank in Turkey also needs to aware on the absence of separate law as the main priority of threats aspect. Another finding shows that separated law and regulation is the main strategies of the study. Concomitantly, the study suggests separate law and regulation as the main strategy to enhance banks participation in Turkey. This study could serve as reference point for the regulator in formulating appropriate policy strategies to increase market share of participatory banks in Turkey.